2021
DOI: 10.1007/s00289-021-03799-3
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ionic liquid)s-based polyurethane blends: effect of polyols structure and ILs counter cations in CO2 sorption performance of PILs physical blends

Abstract: Carbon dioxide (CO 2 ) capture from natural gas, and further utilization is an essential issue for greenhouse gas reduction. Poly(ionic liquid)s (PILs) assemble ILs unique properties, with those of polymers being versatile materials for CO 2 capture from flue gas (CO 2 /N 2 ) and natural gas (CO 2 /CH 4 ). PILs based on polyurethanes obtained with different polyols and ILs cations were blended in different proportions aiming to improve PILs CO 2 sorption capacity. Two different polyols structures (PC and PG) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…In addition, CO 2 has high solubility in IL; however, pure IL has high viscosity and high cost. The polymer-IL thin film not only reduces the high-cost problem in CO 2 absorption, but also improves the absorption capacity and rate [102,103]. Some ILs have excellent biocompatibility and antibacterial properties, which means that the PU-IL materials can be applied in the biomedical field in vivo or in vitro [104,105].…”
Section: Applications Of Pu-ilmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, CO 2 has high solubility in IL; however, pure IL has high viscosity and high cost. The polymer-IL thin film not only reduces the high-cost problem in CO 2 absorption, but also improves the absorption capacity and rate [102,103]. Some ILs have excellent biocompatibility and antibacterial properties, which means that the PU-IL materials can be applied in the biomedical field in vivo or in vitro [104,105].…”
Section: Applications Of Pu-ilmentioning
confidence: 99%
“…The influence of anion and cation structures of IL on the absorption of CO 2 has also been studied. Luz et al [103] prepared two different blends of cationic IL and PU, and the results showed that imidazolium cation was more conducive to the absorption of CO 2 than phosphonium cation. Morozova et al [146] prepared ionic PUs using four different ionic diols with thirteen different counterions and studied the effect of diisocyanate monomers and cation/anion structures on the CO 2 -capturing ability.…”
Section: Carbon Dioxide Capturementioning
confidence: 99%
“…Meanwhile, the existence of CO 2 reduces the exploitation value of natural gas, affects the combustion efficiency of methane, increases cost, and leads to pipeline corrosion [5,6]. Because of this, recovering carbon dioxide from industrial waste gases is crucial for both future use and environmental considerations [7]. Amine absorption is a cutting-edge technology for removing CO 2 , but it has high capital and operating costs, a sophisticated operating method, and will negatively impact the environment [8][9][10].…”
Section: Introductionmentioning
confidence: 99%